Analysis of Labour Market in India : Adoption of the Fourth Industrial Revolution - Anand, Neha; Bhareja, Tushar (Arthshastra Indian Journal of Economics & Research, 2020)
In this paper, we took into consideration the expenditure of the Government of India on the indispensable components of Industry 4.0 namely, telematics, promotion of electronics and HW manufacturing, and cyber security (ICERT, IT Act). The paper attempted to analyze the potential impact of these components of Industry 4.0 on the labour productivity of the India from 2013 – 2018 based on the government funding schemes. Newly – West Estimator was used taking into consideration the problems like multicollinearity and heteroscedasticity. The negative value of the coefficients indicated that the labour productivity is inversely related with the components of Industry 4.0. It was also found out that the government has reduced expenditure in two of the important components of industry 4.0 (telematics and cyber security), while increasing the expenditure in the promotion of electronics and HW manufacturing. The increase in labour productivity in the past 6 years might be due to some other factors in the economy.